Lumpfish (Cyclopterus lumpus) Is Susceptible to Renibacterium salmoninarum Infection and Induces Cell-Mediated Immunity in the Chronic Stage - Gnanagobal, Hajarooba; Cao, Trung; Hossain, Ahmed; Dang, My; Hall, Jennifer R.; Kumar, Surendra; Van Cuong, Doan; Boyce, Danny; Santander, Javier (Frontiers in Immunology, 2021)
Renibacterium salmoninarum is a Gram-positive, intracellular pathogen that causes Bacterial Kidney Disease (BKD) in several fish species in freshwater and seawater. Lumpfish (Cyclopterus lumpus) is utilized as a cleaner fish to biocontrol sea lice infestation in Atlantic salmon (Salmo salar) farms. Atlantic salmon is susceptible to R. salmoninarum, and it can transfer the infection to other fish species. Although BKD outbreaks have not been reported in lumpfish, its susceptibility and immune response to R. salmoninarum is unknown. In this study, we evaluated the susceptibility and immune response of lumpfish to R. salmoninarum infection. Groups of lumpfish were intraperitoneally (i.p.) injected with either R. salmoninarum (1×107, 1×108, or 1×109 cells dose-1) or PBS (control). R. salmoninarum infection kinetics and mortality were followed for 98 days post-infection (dpi). Transcript expression levels of 33 immune-relevant genes were measured in head kidney (n = 6) of fish infected with 1×109 cells/dose and compared to the control at 28 and 98 dpi. Infected lumpfish displayed characteristic clinical signs of BKD. Lumpfish infected with high, medium, and low doses had a survival rate of 65%, 93%, and 95%, respectively. Mortality in the high-dose infected group stabilized after 50 dpi, but R. salmoninarum persisted in the fish tissues until 98 dpi. Cytokines (il1β, il8a, il8b), pattern recognition receptors (tlr5a), interferon-induced effectors (rsad2, mxa, mxb, mxc), and iron regulation (hamp) and acute phase reactant (saa5) related genes were up-regulated at 28 dpi. In contrast, cell-mediated adaptive immunity-related genes (cd4a, cd4b, ly6g6f, cd8a, cd74) were down-regulated at 28 dpi, revealing the immune suppressive nature of R. salmoninarum. However, significant upregulation of cd74 at 98 dpi suggests induction of cell-mediated immune response. This study showed that R. salmoninarum infected lumpfish in a similar fashion to salmonid fish species and caused a chronic infection, enhancing cell-mediated adaptive immune response.